2017
DOI: 10.1016/j.virol.2016.10.023
|View full text |Cite
|
Sign up to set email alerts
|

A naturally occurring variant of HPV-16 E7 exerts increased transforming activity through acquisition of an additional phospho-acceptor site

Abstract: Human Papillomavirus E6 and E7 play critical roles in cancer development, although not all isolates of the viral oncoproteins are identical. A common E7 variant encodes an amino acid change at N29S. We show that this change increases the levels of phosphorylation by CKII by creating an additional phospho-acceptor site at S29. This confers increased phospho-dependent interaction with a number of cellular targets, including TATA Box Binding Protein (TBP) and pRb. A further consequence is an increased ability to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 35 publications
0
22
0
Order By: Relevance
“…Previous studies have shown that the CKII phospho-acceptor site in HPV-16 E7 plays an important role in the HPV life cycle, and in the ability of E7 to bring about cell transformation in a variety of different experimental settings [15, 27]. Furthermore, recent studies showed that a variant HPV-16 E7, in which an extra CKII phospho-site was present at N29S, exhibited a marked increase in transforming potential [20]. Many of these activities have been linked to the effects of phosphorylation on the ability of E7 to interact with some of its cellular substrates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that the CKII phospho-acceptor site in HPV-16 E7 plays an important role in the HPV life cycle, and in the ability of E7 to bring about cell transformation in a variety of different experimental settings [15, 27]. Furthermore, recent studies showed that a variant HPV-16 E7, in which an extra CKII phospho-site was present at N29S, exhibited a marked increase in transforming potential [20]. Many of these activities have been linked to the effects of phosphorylation on the ability of E7 to interact with some of its cellular substrates.…”
Section: Discussionmentioning
confidence: 99%
“…At a molecular level this phosphorylation event is also thought to increase the interaction of E7 with a number of cellular target proteins, including pRb and TBP [16–19]. Indeed, recent studies identified a variant HPV-16 E7 with an extra CKII phospho-acceptor site, and this appeared to correlate with increased transforming potential [20]. Finally, recent structural studies have also begun to shed light on how phosphorylation of E7 might affect its overall structure, and thereby also affect target recognition [21].…”
Section: Introductionmentioning
confidence: 99%
“…For example, CKII phosphorylation of E7 increases the binding affinity of HPV16 E7 for the TATA box-binding protein (TBP) (245), and it is required for efficient transformation by E7 (246). Interestingly, an additional phosphorylation site at serine position 29 exists in a natural E7 variant (N29S) and leads to increased levels of phosphorylation by CKII, which increases the interaction of E7 with TBP and pRb, and its transforming activity in primary rodent cells (247).…”
Section: Transforming Activities Of Pvsmentioning
confidence: 99%
“…There were numerous studies of HPV about cervical lesions, which focused on the relationship between cervical lesions and HPV-related gene and protein, such as L1 protein, L2 protein, E6, and E7 gene. [47] The L1 protein as the main capsid protein of HPV played an important role to recognize the host cell and keep persistent infection, which was a good index to evaluate the infection state in host cell. [8] Previous studies showed that the quantity of L1 protein was declining with aggravate of cervical cell lesion, L1 gene was the coding gene of L1 protein, its methylation was the major reason of L1 protein decreasing, which showed positive correlation to the degree of cervical lesions.…”
Section: Introductionmentioning
confidence: 99%